2018
DOI: 10.1057/s41599-018-0167-8
|View full text |Cite
|
Sign up to set email alerts
|

Religions, poverty reduction and global development institutions

Abstract: Religious traditions have always played a central role in supporting those experiencing poverty, through service delivery as well as the provision of spiritual resources that provide mechanisms for resilience at both the individual and community level. However, the fact that religions can be seen to support social structures and practices that contribute towards inequality and conflict, also underscores a role for religious traditions in creating conditions of poverty. While the Western-led modern global devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…We argue that the labelling of concepts and processes matters if we are to precisely capture the nature of faith-secular partnerships. Characterising the rapprochement we observed as postsecular overlooks the important observation that many faith actors are 'strategically shift [ing]' between secular and religious 'modes of communication' (Tomalin, 2018: 3) as the discussion of our research below demonstrates.…”
Section: Theorising the 'Postsecular' Societymentioning
confidence: 96%
See 2 more Smart Citations
“…We argue that the labelling of concepts and processes matters if we are to precisely capture the nature of faith-secular partnerships. Characterising the rapprochement we observed as postsecular overlooks the important observation that many faith actors are 'strategically shift [ing]' between secular and religious 'modes of communication' (Tomalin, 2018: 3) as the discussion of our research below demonstrates.…”
Section: Theorising the 'Postsecular' Societymentioning
confidence: 96%
“…then take seriously each other's contributions to controversial themes in the public sphere' (Habermas, 2006: 258). While Habermas' idea of a 'complementary learning process' might seem to respect all forms of knowledge and allow individuals to share their perspectives in their own voices, he has been widely criticised for ultimately holding a secularist position when he writes that 'in a constitutional state, all norms that can be legally implemented must be formulated and publicly justified in a language that all the citizens understand ' (2008: 28; see also Dillon, 2012;Tomalin, 2018). For Habermas, this 'publicly justified language' corresponds to reasoned secular discourse that prohibits reference, for instance, to divine authority or revelation, and necessitates that 'religious citizens' ultimately have to translate 'their religious norms into a secular idiom' (Dillon, 2012: 258).…”
Section: Theorising the 'Postsecular' Societymentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly difficult to ignore the role of the socio-economic status in the current level of religiosity in Nigeria because research has identified the impact of religiosity on economic outcomes (Tomalin, 2018;Abdussalam, Johari, & Alias 2015;Aslam, 2014, Hogue, Khan, & Mohammad, 2015Beyes, 2014;Plouff & Tremblay, 2017). Religion is an important cultural and universal social institution that has great influence on people's attitudes, values, and behaviours at both individual and societal levels, while religiosity is the degree to which religion is practised, which can encapsulate all forms and dimensions of religion practises.…”
Section: Introductionmentioning
confidence: 99%
“…In survey research of 114 countries by Gallup (2009), it was discovered that the most highly religious countries are relatively poor with a per-capital GDP below $5000, reflecting a strong relationship between a country's SES and the level of religiosity of the residents. When there are disequilibrium in the economic, political, and social spheres of a country, the consequences of such on the citizens are a high level of stress, unemployment and poverty (Tomalin, 2018). In most developing countries with high level religiosity, there are deficiencies in capital and material resources which inhibit the optimal realization of basic needs such as food, health, education, shelter, and clothing (Ighadalo, 2012, United Nations, 1998.…”
Section: Introductionmentioning
confidence: 99%